Effect of Postoperative High-Concentration Oxygen on Recovery After Thyroid Surgery: A Prospective, Open, Randomized, Controlled Study - Zhou, Qian; Cai, Ming; Gou, Juxiang; Ning, Ning (Frontiers in Endocrinology, 2021)
Objective: To investigate the effectiveness of high-concentration oxygen on the improvement of throat symptoms and voice changes after thyroid surgery and its protection of the parathyroid function. Methods: A total of 600 patients undergoing thyroid surgery who met the inclusion criteria were randomly divided into the experimental group (n = 300) and the control group (n = 300) by using a random number generator. The patients in the experimental group underwent high-oxygen treatment [FiO280 (8 L/min)] for 6 continuous hours after returning to the ward after surgery. The patients in the control group underwent low-oxygen treatment [FiO230 (2 L/min)] for 6 continuous hours after returning to the ward after surgery. Clinical trial registration Number: ChiCTR-IOR-17012765 (China Clinical Trial Registry clinical trial registration center [http://www.chictr.org.cn/index.aspx]) Results: The postoperative incision pain score of patients in the experimental group was significantly better than that in the control group at 6 h (1.07±0.80VS1.23±0.95, P=0.031) and 12 h (1.08±0.64VS1.20±0.73, P=0.041). The postoperative throat pain score of the patients in the experimental group was significantly better than that of the control group at 6 h (1.40±0.85VS1.59±0.97, P=0.011) and 12 h (1.40±0.85VS1.59±0.97, P=0.019). The PONV score of the patients in the experimental group was significantly better than that of the control group at 12 h (0.09±0.19VS 0.14±0.37, P=0.024). The Voice Handicap Index score of the patients in the experimental group was significantly better than that of the control group at 24 h (2.89±5.92VS4.10±6.31, P=0.017), 36 h (2.46±5.06VS3.43±5.97, P=0.035), and 48 h (2.46±5.06VS3.43±5.97, P=0.032). Conclusion: High-concentration oxygen can alleviate PONV and pain after thyroid surgery, with less severe voice changes potentially. However, its effects on swallowing function, and parathyroid function need to be further verified.